Civil Service Pattern in Germany and Ukraine: A Comparative Aspect - DROZD, Oleksiy Yriyovych (Journal of Advanced Research in Law and Economics, 2018)
The article presents a comparative analysis of civil service pattern in Germany, Ukraine and some other European countries; are identified the key differences determining the civil service pattern in the above-mentioned countries.